Uso da ecocardiografia Doppler na análise evolutiva da cardiopatia reumática e no suporte à decisão de suspender a profilaxia secundária de pacientes com febre reumática - Fatima Derlene da Rocha Araujo (2012)
Acute rheumatic fever (ARF) and rheumatic heart disease (CRC) are still the leading cause of acquired heart disease in young people in developing countries. The diagnosis remains based on clinical criteria and changes in laboratory tests are only auxiliary. But with the advent of Doppler echocardiography, it has been used systematically in the evaluation of valvular alterations, aiding in the diagnosis and monitoring. Objectives: To characterize the clinical and Doppler echocardiographic profiles of patients with rheumatic fever in acute and chronic phases and define prognostic factors of significant valvular heart disease. To evaluate the Doppler echocardiographic findings in those with normal clinicalexamination, at least five years after the first episode, and to discuss thecontribution of Doppler echocardiography in supporting the decision todiscontinues secondary prophylaxis. Methodology: Longitudinal studyincluding 462 patients diagnosed with rheumatic fever according to Jones criteria, and followed up from the initial attack to 13.6 ± 4.6 years. All patients underwent clinical evaluation and Doppler echocardiography in acute and chronic phases. In the subsequent phase of the study, 183 patients who had normal clinical examination, after five or more years of the initial outbreak, underwent Doppler echocardiographic assessment and classified the degree of mitral valve disease and aortic valves. According to current recommendations, the withdrawal of secondary prophylaxis was evaluated and included Doppler echocardiographic criteria. Categorical variables were compared using the chi square (2) test or Fisher test, with the significance level set at p£0.05, and analyzed using univariate and multivariate logistic regression analyses. The Kappa index was used for agreement analyses. Results: Their ages in the first attack ranged from three to 17 years (mean of 9.4 ± 2.4 years) with a median of 10 years, 56.5% were female. Carditis occurred in 55.8% and subclinical valvulitis in xxiv 35.3%. In the chronic phase, 33% of the heart valve lesions were moderate to severe. No improvement was observed on Doppler echocardiography as regards severe valvulitis, although heart auscultation had become normal in 13% of patients. In the multivariate analysis, only severity of carditis and mitral and/or aortic valvulitis were associated with significant valvular heart valve. Chorea or arthritis were protective factors for significant valvular heart disease: odds ratio 0,41 (95% C.I. 0,22 0,77) and 0,43 (95% C.I. 0,23 0,82), respectively. In the analysis of 183 patients with normal cardiac auscultation, after five or more years of diagnosis, subclinical chronic heart disease occurred in 79% of patients who had carditis and 25% of those without carditis. Of the 35 (36%) patients who had carditis had definite signs of residual valve disease in 13 (37%) and mild in 22 (63%), but in no patient Doppler echocardiographic examination was normal. Already in 62 (64%) patients who had not carditis, only two (3%) had a final residual valve disease, 15 (24%) mild and 45 (73%) had normal results. When added to the morphological criteria associated with Doppler, prophylaxis was maintained at 13 (37%) of patients who had carditis and in only two (3%) of those without carditis. Conclusion: The degree of heart valve involvement on clinical examination (carditis) and Doppler echocardiography (valvulitis) in the initial attack is an important prognostic factor and identifies patients to whom secondary prophylaxis should be stricter. In the chronic phase, the normalization of cardiac auscultation is not always accompanied by normalization of the Dopplerechocardiographic findings. In the assessment of the withdrawal ofsecondary prophylaxis, the isolated use of Doppler criteria are not suitable for diagnosis of valvular heart disease, should be added criteria for evaluation of mitral valve morphology.